A Comparative Study on Group-Based Learning Using STAD and SGD Toward Students’ Writing Achievement of Descriptive Text - Wahyuni, Sri (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2018)
This study discusses a comparative study of group-based learning method between STAD and SGD toward students’ writing achievement of descriptive text on the tenth grade of SMK SalafiyahKajen in the academic year of 2017/2018. The purpose of the study was to differentiate those two methods, which were then found the appropriate method between STAD and SGD for learning writing skill. This study used a mixed method by using comparative design. The subject of this study were the students at the tenth grade of SMK SalafiyahKajen, students’ class RPL 2 and TB. The students from both of the class had different treatment which RPL 2 was treated using SGD and TB was treated using STAD. The technique of data collection was a test, observation, and documentation. The test consisted of two tests; they were pre-test and post-test. After collecting the data, it was found that the average score of pre-test of SGD group was 50.06 and for STAD group was 47.75; meanwhile, the average score of post-test of SGD group was 68.70 and for STAD group was 63.10. So, the computation of t count was 5.031, and the t table was 1.69. The t count was higher than t table, which stated that Ha was accepted. It meant that there was a significant difference between students' writing achievement which was taught by using STAD and SGD. The conclusion defined that SGD was better than STAD to be applied in learning writing.